Demographic Characteristic of Fundic Gland Polyp and Its Association with Gastritis in Pathology Anatomy Department, Faculty of Medicine, Universitas Indonesia/Cipto Mangunkusumo Hospital - Liza Handayani; Ening Krisnuhoni (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Fundic gland polyp (FGP) is the most common polyp found in the stomach with the incidence of 47% from all stomach polyps. FGP is more common to be found in female with the ratio of 5:1 and occurs in the average age of 53-year-old. Gastrin is a hormone produced by G cell, which function is to facilitate epithelial cell proliferation. Gastritis is a frequently found digestive tract disturbance. Torbenson et al showed the presence of chronic gastritis in FGP patients. The aim of this study is to observe the demographic characteristics of FGP and to identify the association between number of polyps with morphologic appearances of gastritis in Anatomical Pathology Department, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital in year 2012-2014.Method: This retrospective study was a descriptive analytical study. This study was performed by reviewing the slides of FGP cases and evaluating the severity of gastritis based on visual analog scale from Sydney System (SS).Results: Study of FGP demographic obtained 44 cases with predominantly female aged 30 (68.2%), patients’ average age was 55.4 year old with dominant age group in age group 51-60 year old which accounted for 16 (36.4%). This study was performed in 38 cases. The frequency of single polyp was 18 and multiple polyp was 20. Most cases were chronic inflammation which accounted for 21 (55.3%) and mild atrophy 18 (47.4%). Mild intestinal metaplasia was found in 1 case. There was no case of neutrophil infiltration, H. pylori infection or dysplasia. Chi-square test revealed that there was no significant association between number of polyps with gastritis.Conclusion: Chi-square test which was performed in this study showed there is no significant association between number of polyps with gastritis.